Possible Approaches to Organizing Self-Test of a Self-Routing Analog-To-Digital Converter Based on a Neural Network - Naborshchikov, Anton A.; Yuzhakov, Alexander A.; Posyagin, Anton I. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2022)
The article provides a review of the literature on the development of a self-routing analog-to-digital converter (ADC) based on a neural network (SRADC NN). The advantages and disadvantages of SRADC NN are described. Approaches to the implementation of self-testing algorithms of the device are proposed, as well as the purpose and objectives for further research are formulated.